High-resolution X-ray computed tomography of through silicon vias for RF MEMS integrated passive device applications. Issue 9 (August 2015) - de Veen, P.J.; Bos, C.; Hoogstede, D.R.; Revenberg, C.Th.A.; Liljeholm, J.; Ebefors, T.
Abstract: This paper presents our exploration of microfocus and high-resolution X-ray computed tomography (CT) on open high-aspect ratio through Silicon via (TSV) test structures, the interior wall covered with a ~ 10 μm thick conformal Cu plating, using state-of-the-art and commercially available X-ray systems. Goal of our research is to better understand the physical failure mechanisms of defective open TSVs, in order to further improve the yield of TSV production for integrated passive devices (IPD) to be used in radio frequency microelectromechanical system (RF MEMS) applications. Micrometer-sized defects were non-destructively identified in some of the open TSVs (i.e. Cu plating thickness deviations, incomplete plating and large voids) using microfocus X-ray CT, which were then verified by destructive mechanical cross-sectioning. With high-resolution X-ray CT, which has almost an order of magnitude better resolution, (sub) micron-sized defects in TSVs were directly non-destructively identified and localized, without the need for further destructive inspection techniques for confirmation. The Cu plating thickness variations, in TSVs all connected to a large-area redistribution layer, were found to be design related; based on these failure analysis findings, a new electroplating procedure has been established. Highlights: Exploration of microfocus and high-resolution X-ray computed tomography on open through silicon vias test structures. Submicron-sized defects in Cu-plating of open TSVs were non-destructively localized with HR X-ray CT. Identified defects were verified by destructive mechanical cross-sectioning. Improved yield of TSV production for RF MEMS integrated passive device applications. A new electroplating procedure has been established, based on these failure analysis findings.